Prevalence of burnout in soccer athletes of the sub-20 category along a sports season - Camila Cristina Fonseca Bicalho; Israel Teoldo da Costa; Franco Noce; Varley Teoldo Costa (Revista da Educação Física)
The aimed of the study were: (a) to construct a reference table for burnout in soccer athletes of the U-20 category and (b) to verify the individual oscillations in the perception of these athletes in relation to burnout over three periods of the sports season. The 53 sub-20 soccer athletes participated. The Atlhete Burnout Questionnaire, brazilian version, was applied to athletes during training, competition and vacation periods of the sports season. A reference table was built for under-20 soccer athletes for each assessed period. Fluctuations were found in the average values of the total burnout frequency of the athletes during the 3 periods: training (=1.35 ± 0.13 and =2.11 ± 0.19), competition (=1.26 ± 0.13 and =2.27 ± 0.24) and vacation (=1.27 ± 0.14 and = 2.18 ± 0.28) Based on this table and the individual classification of each athlete, it was observed that 32 athletes presented fluctuations in the perception of burnout during the sports season and 21 athletes did not show fluctuations in feelings of burnout during the three evaluation periods. The period with the highest number of athletes (n = 17) with a high level of burnout was the training period. It is concluded that it is not possible to establish a single and collective behavior regarding the fluctuations of burnout levels in athletes of the U-20 category during a sports season, and that the category reference table contributes to a greater accuracy of the burnout evaluation in every season.